The Effectiveness of Cognitive Conflict-Based Chemistry Learning in Reducing Students' Misconceptions of Acid-Base Materials - Lis Setiyo Ningrum; Apriliana Drastisianti; Hanifah Setiowati; Resi Pratiwi (Jurnal Penelitian Pendidikan IPA, 2022)
A misconception is a problem that is often encountered in the world of education caused by several things, including students' initial prejudices, incompetent teachers, unclear textbooks, different contexts of the student experience, and teaching methods that only contain lectures. This study is intended to answer the problem regarding the effectiveness of cognitive conflict-based chemistry learning in reducing students' misconceptions about acid-base material. This research is quasi-experimental research with One group Pre-test and Post-test Design. The population in this study was all class XI IPA. The sample in this study was class XI IPA I. The instrument used in this study was a student's concept understanding test. The data collection method used is a multiple-choice reasoned test method. Changes in misconceptions were analyzed descriptively and statistically. A descriptive analysis was conducted to see changes in students' concepts. Statistical analysis using the T-test. Based on the research, it was found that the indicators of questions that experienced misconceptions were: Arrhenius acid-base theory (32.05%), Arrhenius acid-base classification (56.40%), Bronsted Lowry theory (43.59%), writing down the acid-base reaction equation according to Bronsted Lowry and Lewis acid-base theory (59.00%), distinguish between Arrhenius, Bronsted Lowry and Lewis acid-base theories (49.00%), the nature of acidic and basic solutions (47.00), degree of acidity/pH (79.00%), determination of strong acid (79.00%), determination of strong base (46.00%), degree of ionization in acid and base determination (46.00%) and application of the concept of pH in pollution (66.00%). Understanding of students' initial conceptions, namely students who are classified as knowing the concept of 23.18%, misconceptions of 53.95%, and not knowing the concept of 22.87%, while the understanding of the final conception of students is students who are classified as knowing concepts of 76, 20%, a misconception of 15.49% and not knowing the concept of 8.31%. Based on these data, it can be concluded that the cognitive conflict learning method is effective in reducing students' misconceptions